Tantangan dan Kebutuhan Satuan Pendidikan dalam Implementasi Pendidikan Inklusif bagi Anak Berkebutuhan Khusus di Sumatera Utara - Felicia Joice Sitinjak; Asril Rouli Nilawati Pasaribu; Elsa Monica Br Sirait; Irenita Br Perangin Angin; Widia Wati Sipayung; Elsah Sinurat; Tesa Arizky Simanjuntak; Lili Tansliova (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Inclusive education in North Sumatra faces various challenges in its implementation, especially in meeting the needs of children with special needs (ABK). This study aims to identify the challenges and needs of educational units in implementing inclusive education for ABK. The research method used is qualitative with a case study approach, involving in-depth interviews with teachers, principals, parents, and education stakeholders. The results of the study indicate that the main challenges include the lack of understanding and readiness of teachers in handling ABK, limited supporting facilities and infrastructure, and minimal adequate training and resources. On the other hand, the main needs identified are increasing teacher capacity through special training, providing accessible facilities, and strong policy support from the local government. This study concludes that to achieve successful implementation of inclusive education, collaboration between the government, schools, parents, and the community is needed in overcoming challenges and meeting existing needs. Recommendations submitted include strengthening teacher training programs, increasing budget allocation for facilities and infrastructure, and more intensive socialization of the importance of inclusive education for all levels of society.